ASSOCIATION BETWEEN THE FIB-4 INDEX AND RENAL FUNCTION IN PATIENTS WITH TYPE 2 DIABETES MELLITUS (Vietnam Journal of Community Medicine, 2026)
Objectives: To investigate the association between the FIB-4 index and renal function in patients with type 2 diabetes mellitus.Subjects and methods: A descriptive cross-sectional study was conducted in 130 patients diagnosed with type 2 diabetes mellitus who attended the Outpatient Department of University Medical Center Ho Chi Minh City - Campus 2. The FIB-4 index was calculated using age, AST, ALT, and platelet count.Results: Among 130 patients with type 2 diabetes mellitus, FIB-4 was significantly negatively correlated with eGFR (r = -0.25; p = 0.0038), total cholesterol (r = -0.29; p = 0.001), and LDL-C (r = -0.27; p = 0.002). In the multivariable linear regression model, higher FIB-4 (β = -8.36; p = 0.001) and lower hemoglobin (β = 5.17; p < 0.001) were independently associated with decreased eGFR. In the multivariable logistic regression model, FIB-4 (p = 0.005) and hemoglobin (p = 0.003) remained independent predictors of eGFR < 60 mL/min/1.73 m², with an AUC of 0.7284.Conclusions: The FIB-4 index and hemoglobin were independently associated with impaired renal function in patients with diabetes. In clinically stable conditions and in the absence of acute liver injury, FIB-4 may serve as a simple and useful marker for early identification of chronic kidney disease risk in clinical practice.
Keywords: FIB-4, renal function decline, type 2 diabetes mellitus.